Prevalence and Risk Factors of Occupational Contact Dermatitis in Healthcare Workers - Enggalhardjo, Muljani; Setiawan, Alan Dwi; Christianto, Putra Niko Laksamana Oceano (Medicinus, 2024)
Background: Occupational contact dermatitis (OCD) is prevalent among healthcare workers, especially during the COVID-19 pandemic. Symptoms include dryness, itchiness, and redness, with hands being the most affected. Risk factors include frequent hand washing, increased glove use, allergies, and lack of health and safety training. This review emphasizes the need for targeted prevention strategies and awareness programs.Methods: We conducted a systematic review using PubMed, focusing on studies involving healthcare workers and OCD. Keywords included "occupational contact dermatitis," "contact dermatitis," "healthcare workers," and "risk factors for OCD." Data were collected using a structured, interviewer-administered questionnaire, including the Nordic Occupational Skin Questionnaire (NOSQ-2002).Result: The review included 2,706 healthcare workers. Hand dermatitis was the most common, affecting 22% of participants. Key risk factors were a personal history of allergies, frequent hand washing, high glove usage, and insufficient health and safety training.Conclusions: This review identifies significant risk factors for OCD among healthcare workers, highlighting the need for interventions focused on reducing hand washing frequency, managing glove use, and improving health and safety training.